Robust Multi-Object Detection Based on Data Augmentation with Realistic Image Synthesis for Point-of-Sale Automation - Koturwar, Saiprasad; Shiraishi, Soma; Iwamoto, Kota (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
As an alternative to bar-code scanning, we are developing a real-time retail product detector for point-of-sale automation. The major challenge associated with image based object detection arise from occlusion and the presence of other objects in close proximity. For robust product detection under such conditions, it is crucial to train the detector on a rich set of images with varying degrees of occlusion and proximity between the products, which fairly represents a wide range of customer tendencies of placing products together. However, generating a fairly large database of such images traditionally requires a large amount of human effort. On the other hand, acquiring individual object images with their corresponding masks is a relatively easy task. We propose an realistic image synthesis approach which uses individual object images and their corresponding masks to create training images with desired properties (occlusion and congestion among the products). We train our product detector over images thus generated and achieve a consistent performance improvement across different types of test data. With the proposed approach, detector achieves an improvement of 46.2% (from 0.67 to 0.98) and 40% (from 0.60 to 0.84) over precision and recall respectively, compared to using a basic training dataset containing one product per image.